The Dark Web: What Is It, How to Access It, and Why We Need to Study It. (May 2023) - Ngo, Fawn T.; Marcum, Catherine; Belshaw, Scott
The dark web is a subsection of the deep web that conventional search engines cannot index. As an encrypted network of websites, the dark web can only be accessed using special browsers such as Tor. Tor, formerly an acronym for "The Onion Router, " is a free and open-source software intended to protect the personal privacy of its users and keep their internet activities unmonitored. While the dark web is known for both legitimate and illegitimate purposes, it remains notorious for facilitating illegal and deviant activities ranging from drug dealing to child pornography, human trafficking, arms dealing, and extremist recruitment. Accordingly, researching and understanding the dark web is a critical and essential step in fighting and preventing cybercrime. However, studying the dark web poses unique challenges. This special issue seeks to provide a platform for researchers and criminologists to share and discuss research designs and methods that help shed light on the actual activity going on in the dark web's shadowy realms.